RELAKSASI PERNAFASAN MENURUNKAN NYERI PADA IBU PASCA SEKSIO SESAREA - Ningsih, Dewi Aprilia (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
Research purposes to determine the effect of relaxation breathing to changes in post-cesarean pain. This study uses a quasi-experimental in one group (one group pretest posttest design). The independent variable is the dependent variable breathing and relaxation is pain post caesarean section. The population numbered 157 people with a total sample of 46 people. The research was conducted in the Obstetric Hospital Dr.M.Yunus C1 Bengkulu on 5 December 2012-15 January 2013. Data were analyzed by Paired t-test dependent. Statistical test results showed an average pain level was 6.02 before the intervention and after intervention the average pain intensity was 3.98. Bivariate results obtained p value = 0.000 with the mean difference was 2.04, indicating a decline in the average post-Caesarean section pain after breathing relaxation techniques.